Assembly of Peptides Derived from β-Sheet Regions of β-Amyloid - Truex, Nicholas L. (J Am Chem Soc, 2016)
[Image: see text] In Alzheimer’s disease, aggregation of the β-amyloid peptide (Aβ) results in the formation of oligomers and fibrils that are associated with neurodegeneration. Aggregation of Aβ occurs through interactions between different regions of the peptide. This paper and the accompanying paper constitute a two-part investigation of two key regions of Aβ: the central region and the C-terminal region. These two regions promote aggregation and adopt β-sheet structure in the fibrils, and may also do so in the oligomers. In this paper, we study the assembly of macrocyclic β-sheet peptides that contain residues 17–23 (LVFFAED) from the central region and residues 30–36 (AIIGLMV) from the C-terminal region. These peptides assemble to form tetramers. Each tetramer consists of two hydrogen-bonded dimers that pack through hydrophobic interactions in a sandwich-like fashion. Incorporation of a single (15)N isotopic label into each peptide provides a spectroscopic probe with which to elucidate the β-sheet assembly and interaction: (1)H,(15)N HSQC studies facilitate the identification of the monomers and tetramers; (15)N-edited NOESY studies corroborate the pairing of the dimers within the tetramers. In the following paper, J. Am. Chem. Soc.2016, DOI: 10.1021/jacs.6b06001, we will extend these studies to elucidate the coassembly of the peptides to form heterotetramers.